FORMATION OF STUDENTS' COMPETENCE IN THE USE OF CLOUD TECHNOLOGIES IN THE INFORMATION EDUCATIONAL ENVIRONMENT - Mamarajabov Odil Elmurzaevich (Scholar Express Journal, 2022)
The use of cloud technology allows you to reduce the cost of the reading process, the formation of teaching materials, providing access to it, improve the quality of reading on account of the rapid change of curriculum.
Keywords: Cloud technology; Storage as a Service; Platform as a Service; SECI